Drug dreams : clinical and research implications of dreams about drugs in drug-addicted patients - Colace, Claudio (Karnac, 2014)
"'Drug dreams', or the dreams in which drug-dependent patients use or attempt to use the drugs that they are addicted to, are a well-documented clinical phenomenon in various forms of drug addiction. Authors have highlighted their clinical, prognostic and therapeutic usefulness, since they provide information about the patients' 'drug craving', their ability to cope with it, and their motivation to stay clean and sober. However, the study of drug dreams also reveals several implications and inspiration for general dream research and theory, especially with respect to the recent neuropsychology of dreaming, the emotional adaptive theories of dream, and the classical Freudian theory of dreams. This book is aimed at providing a systematic and comprehensive discussion on drug dreams by considering the various perspectives involved (such as therapy in drug addiction, the neurobiology of drug craving, affective neuroscience, dream research) and, ideally, at suggesting future clinical applications for therapists (counsellors, psychoytherapists, clinicians) in charge of treating drug-addicted patients, as well as providing input for dream researchers. The book draws from the author's clinical and research experience on drug dreams among heroin-addicted patients, as well as from the scientific literature in this field. The book is composed of three parts: the phenomenology of drug dreams, their clinical and therapeutic aspects, and their implications for the dream research and theory"--Provided by publisher.